Gonadotropin inhibitory hormone (GnIH) prevents the ‘priming’ effect of estradiol-17β - Ika Puspita Sari; Jessica Jacobi; Alexandra Rao; Iain Clarke (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2011)
GnIH inhibits GnRH-stimulated gonadotropin secretion in the sheep by action on the pituitary gonadotropes. Estradiol-17β(E2) also acts at the level of the pituitary gonadotrope to exert negative and positive feedback effects on gonadotropin secretion. The positive effect facilitates the estrogen-induced surge in gonadotropin releasing hormone (GnRH) and LH. This study was undertaken to determine whether this ‘priming’ effect of E2 is prevented by GnIH. Cultured pituitary cells were treated with GnRH or vehicle every 4 h for 24 h with and without GnIH and E2 treatment. GnRH stimulated (LH) and follicle stimulating hormone (FSH) secretion was increased by E2 treatment. The effect of E2 was overcomes by the inhibitory effect of GnIH. We conclude that GnIH may counteract the priming effect of E2 on pituitary gonadotropes.Key words:Gonadotropin, gonadotrope, gonadotropin inhibitoryhormone, estradiol